Silicon alleviates the changes in the source-sink relationship on wheat plants infected by Pyricularia oryzae - Araujo, Marcela Uli Peixoto (2017)
Blast, caused by Pyricularia oryzae, has become an economically important disease on wheat in Brazil. Alternative methods for blast management are demanded by the growers and silicon (Si) stands out for its potential to decrease the intensities of important diseases in several crops. The present study aimed to investigate the effect of Si in improving the production of photoassimilates on flag leaves and their partitioning to spikes in a scenario where the blast symptoms will be lowered due to the potentiation of mechanisms of defense by this element on the source-sink interface. Wheat plants (cultivar BRS-Guamirim) were grown in hydroponic culture with either 0 or 2 mM Si and plants were inoculated with P. oryzae at 10 days after anthesis. The Si concentration on flag leaves and spikes of plants supplied with Si increased and contributed to decrease disease symptoms. Higher concentrations of total soluble phenolics and lignin-thioglycolic acid derivatives and greater activities of peroxidases, polyphenoloxidases, phenylalanine ammonia-lyases, β-1,3- glucanases and chitinases were noticed on flag leaves and spikes of plants supplied with Si and contributed to their resistance to blast. There was less concentration of pigments and an impairment of the photosynthetic performance of infected flag leaves and spikes from plants non-supplied with Si based on the values for the chlorophyll a fluorescence parameters maximal photosystem II quantum efficiency, fraction of energy absorbed used in photochemistry, quantum yield of non-regulated energy dissipation and quantum yield of regulated energy dissipation. On infected flag leaves and spikes from plants non-supplied with Si, the concentration of soluble sugars was lower while the hexoses-to-sucrose ratio increased on infected flag leaves. The sucrose phosphate synthase activity was lower while higher expression and activity of acid invertases was higher and lower, respectively, on flag leaves and spikes of plants non-supplied with Si in comparison to Si-supplied plants. The starch concentration on spikes of plants supplied with Si increased. All together, the results from the present study confirm the active role played by Si in increasing wheat resistance to blast, but present novel evidences of the effect of this element in improve the source-sink relationship on infected flag leaves and spikes by preserving the alterations in assimilate production and partitioning during the grain filling process.